Contemporary issues in Qiwamah within the family institution - Yunus, Saidatolakma (Contemporary Fiqh Research Unit, IIUM & Islamic Book Trust, 2025)
Qiwamah is the foundation for building a Muslim family. We cannot establish a stable and excellent nation without first building a stable family, as it ensures family stability and educational well-being within a Muslim family. However, there has been widespread debate in understanding its meaning, especially among those influenced by modernist and orientalist ideas. Therefore, this topic is of great importance and deserves special attention so that it can be properly understood.